The Parsee Mazagaon Anjuman Daremeher - Mumbai Archive Project Team (Jio Institute, 2024)
The Parsee Mazagaon Anjuman Daremeher caters to the religious needs of the Parsi community in the Mazagaon area. The two-storey building, designed in the Gujarati architectural style, is entered through a triple-arched veranda facing the street. The first floor has a wooden balcony with a sloping tiled roof.